Visualizing and Understanding the Components of Lagrange and Newton Interpolation. Issue 1 (2nd January 2016) - Yang, Yajun; Gordon, Sheldon P.
Abstract: This article takes a close look at Lagrange and Newton interpolation by graphically examining the component functions of each of these formulas. Although interpolation methods are often considered simply to be computational procedures, we demonstrate how the components of the polynomial terms in these formulas provide insight into where these formulas came from, why they work, and how they should be used.